2013
DOI: 10.1007/s00216-013-7374-3
|View full text |Cite
|
Sign up to set email alerts
|

A novel electrochemical method for efficient reduction of disulfide bonds in peptides and proteins prior to MS detection

Abstract: A novel electrochemical (EC) method for fast and efficient reduction of the disulfide bonds in proteins and peptides is presented. The method does not use any chemical agents and is purely instrumental. To demonstrate the performance of the EC reactor cell online with electrospray mass spectrometry, insulin and somatostatin were used as model compounds. Efficient reduction is achieved in continuous infusion mode using an EC reactor cell with a titanium-based working electrode. Under optimized conditions, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 37 publications
2
71
0
Order By: Relevance
“…The SH content after electric stove heating was slightly lower than for the induction cooker, due to the stronger thermal effect of the electric stove over the induction cooker (Table ) (Wang and Damodaran ). Several reports (Zhang and others ; Kraj and others ; Mysling and others ) have used square‐wave pulse (potentials were −1.5 V [1990 ms] and +1.0 V [1010 ms]) to efficiently reduce the SS bonds (μM/nM level) to SH. In this study, alternating current (220 V, 50 Hz), which was somewhat similar to square‐wave pulse, was used to treat 400 g of raw soymilk.…”
Section: Resultsmentioning
confidence: 99%
“…The SH content after electric stove heating was slightly lower than for the induction cooker, due to the stronger thermal effect of the electric stove over the induction cooker (Table ) (Wang and Damodaran ). Several reports (Zhang and others ; Kraj and others ; Mysling and others ) have used square‐wave pulse (potentials were −1.5 V [1990 ms] and +1.0 V [1010 ms]) to efficiently reduce the SS bonds (μM/nM level) to SH. In this study, alternating current (220 V, 50 Hz), which was somewhat similar to square‐wave pulse, was used to treat 400 g of raw soymilk.…”
Section: Resultsmentioning
confidence: 99%
“…However, other methods have been reported that are equally applicable, including reagents such as performic acid [20], sodium sulfite [21], and tris(2-carboxyethyl)phosphine (TCEP) [16]. More recent advances include electrochemical methods [22-23]. …”
Section: Resultsmentioning
confidence: 99%
“…In the EC-ESI-MS study, many experimental parameters that affected the disulfide-bond-reduction efficiency were identified, including square-wave potential settings, electrode material, solution composition and flow rate. One improvement for disulfidebond reduction is to use square-wave pulses rather than constant potentials [69,70]. The squarewave pulse plays an important role in avoiding electrode fouling and keeping the electrode clean for maintaining high-efficiency reduction.…”
Section: Coupling Of Ec-ms With Liquid-sample Desimentioning
confidence: 99%
“…The squarewave pulse plays an important role in avoiding electrode fouling and keeping the electrode clean for maintaining high-efficiency reduction. For example, using square-wave pulsing, the efficiency of disulfide reduction for insulin reduction was calculated as over 98% [69]. In addition, the most suitable electrode for disulfide reduction was found to be a Ti-based electrode.…”
Section: Coupling Of Ec-ms With Liquid-sample Desimentioning
confidence: 99%